Pengaruh Subscribe Terhadap Keputusan Pembelian Produk Digital (Studi pada Mahasiswa Pasca Sarjana Perguruan Tinggi Di Malang) - Riza Khusniah (Politeknik Negeri Batam, 2013)
Inside marketing is one method of alternative marketing in the internet. Inside marketing is a relation which has regular steps and continous relationship. We can retain the customers who have visited our website. In inside marketing we can use subscribe to do this. We have to remember that content of subscribe can be suited to follow the company’s purposes. There are so many functions of subscribe such as follow up, inform new product, promotion, etcetera. The conclusion of this research is that subscribe affect simultaneously on the decision of buying of digital products. While partially are the inspirational email and the information email influence the decision to buy digital products. As for the promotion email had a little effect on product of buying decision of digital products.